Tourism in China destinations, planning and experiences - Ryan, Chris; Huang, Songshan (Sam) (Buffalo, NY Channel View Publications, 2013)
This book offers an in-depth understanding of tourism development and destination planning in China's transitional economy. It is a unique collaboration between editors and contributors to present issues in current Chinese tourism research to Western colleagues. The influences informing the book range from pragmatic concerns about destination planning in China, to senses of injustice about how that planning generates unequal distributions of revenue via concerns about needs for new conceptual approaches. The book also examines the changing nature of Chinese society and its political system, and commentary on the changing role of the Chinese State in tourism planning. It will be a valuable resource for postgraduate students and tourism researchers as well as for tourism industry professionals who want to understand China as a domestic, outbound, and inbound tourism market
Includes bibliographical references and index.
Keywords: Tourism -- China -- Planning; Tourism -- China -- Management